EFFECT OF DOUBLE HYPOGLYCEMIC THERAPY WITH METFORMIN AND SAXAGLIPTIN, ON ACHIEVEMENT OF GLYCEMIC CONTROL IN PATIENTS WITH TYPE 2 DIABETES AND ADJUVANT OBESITY - Nikulina , Liliia (The Ukrainian Scientific Medical Youth Journal, 2018)
The main goals of the current research on the management of patients with type 2 diabetes are the assessment of the effects of early intensive glycemic control on the development and progression of the disease and its complications and the discovery of the clinical benefits of various types of hypoglycemia. Given the convincing evidence of beneficial effects on the course of the disease, inhibitors of dipeptidyl peptidase-4, primarily saxagliptin, should be considered as a group of first-line hypoglycemic therapy, along with metformin, in the treatment of patients with high-risk type 2 diabetes with concomitant diseases. In a study involving 31 patients with type 2 diabetes, obesity and inadequate glycemic control, on the background of recommended monotherapy metformin, the effectiveness of combination therapy with saxagliptin and metformin was demonstrated. The comparison group consisted of 29 patients with monotherapy metformin at a dose of 2000 mg per day. In most patients receiving saxagliptin at a dose of 5 mg in combination with metformin, a decrease in HbA1c, glucose uptake and postprandial glycaemia was observed compared to baseline values. These results were also more significant compared to the metformin monotherapy group. In addition, the appointment of combination therapy contributed to the improvement of functional activity of  - cells of the pancreas. The obtained results allow us to recommend this scheme of combination therapy for the management of patients with type 2 diabetes with obesity.